Barriers to total quality management (tqm)-Implementation in the mauritian food industry - Shameer, Danyen; Sing, Callychurn (Cranfield University Press, 2013)
This study was undertaken to determine some of the barriers to the implementation of total quality management (TQM) in the population of medium to large Mauritian food manufacturing companies (MFMC), which were then compared with those identified in Indian and USA manufacturing industries. For this purpose, a questionnaire was sent to the population via e-mail. After carrying out exploratory factor analysis and reliability test, all constructs/investigated barriers were found to be valid and reliable. On comparing the mean ratings for the barriers, the local companies obtained the lowest mean rating that was significantly different (p<0.05) from Indian and USA manufacturing companies. This showed that these barriers had not yet impacted greatly in MFMC. However, the two potential obstacles identified in the Mauritian context were: employee’s resistance to change and frequent turnover of employees.
Keywords: Food manufacturing industry; Total Quality Management; barriers